Local in Education Policy Discourse in India - Gulati, Nidhi; Jain, Manish (Voices of Teachers and Teacher Educators, 2021)
This article looks at how local, as a concept, relates to education in the framework of National Education Policy (NEP) 2020. To examine this, the paper is divided into five sections. It focusses on the urge for ‘local’ as an aesthetic. It provides a historical overview of the idea of local in the context of and in relation to education from colonial to contemporary times with attention to various policies, reports and ‘innovative’ programmes. It highlights how contemporary debates have been influenced by global players and ideologies. The paper explains how local as a leitmotif operates in NEP 2020 and offers suggestions to give space to it in policy implementation.